Study of Short Channel Effects in n-FinFET Structure for Si, GaAs, GaSb and GaN Channel Materials - Tawseef A. Bhat; M. Mustafa; M.R. Beigh (Журнал нано- та електронної фізики)
In this paper a study of various short channel effects (SCE’s) of double gate n-FinFET structure as a function of scaling parameters for Si, GaAs, GaSb and GaN channel materials has been evaluated and presented. The simulation results presented are based on the self consistent solution of Poisson and drift-diffusion equations. In the model the carrier velocity is assumed to be saturated in the channel for all the materials. Gate length (Lg) and channel width (Wch) dependence of the various short channel effects viz., Drain Induced Barrier Lowering (DIBL), Subthreshold Slope (SS) and threshold voltage roll-off of these devices using the said materials have been studied and presented.